The influence of learning organization on employee performance mediated by employee creativity at pertamina hulu rokan, riau - Fauzia, Sabila Hayyu; Wijayanto, Andi; Listyorini, Sari (Institute of Computer Science (IOCS), 2025)
This study aims to analyze the influence of learning organization on employee performance, with creativity as a mediating variable, at PT Pertamina Hulu Rokan in Riau. In facing business challenges in the energy sector that are constantly changing dynamically, companies need to develop a structured knowledge management system to improve the adaptive capabilities and productivity of their human resources. The approach used in this study is a quantitative approach with an explanatory research method, which aims to explain the causal relationship between variables. The sample in this study consisted of 100 respondents who were employees of PT Pertamina Hulu Rokan, selected through purposive sampling techniques. The data collection instrument was a questionnaire with a 5-point Likert scale, and the data analysis technique used Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of SmartPLS software. The results of the study showed that knowledge management had a positive and significant effect on employee creativity. Creativity has also been shown to have a positive effect on improving employee performance. In addition, knowledge management also directly affects performance, and creativity acts as a partial mediator in the relationship. These findings indicate that the development of a learning organization based on a knowledge system will increase employee creativity, which in turn is able to drive continuous performance improvement. This study contributes both theoretically to the development of literature related to knowledge management and creativity, as well as practically as a basis for managerial decision making in building an innovative and knowledge-based work culture